2017
DOI: 10.1016/j.molcel.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Granule Transcriptome Reveals Principles of mRNA Accumulation in Stress Granules

Abstract: SUMMARY Stress granules are mRNA-protein assemblies formed from nontranslating mRNAs. Stress granules are important in the stress response and may contribute to some degenerative diseases. Here we describe the stress granule transcriptome of yeast and mammalian cells through RNA-Seq analysis of purified stress granule cores and smFISH validation. While essentially every mRNA, and some ncRNAs, can be targeted to stress granules, the targeting efficiency varies from <1% to >95%. mRNA accumulation in stress granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

92
931
7
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(1,081 citation statements)
references
References 55 publications
92
931
7
4
Order By: Relevance
“…Recruitment of mRNAs to stress granules is sequestered from translational sites, a process induced by cellular stress (Khong et al . ). This is consistent with the general association of m6A with translational activation.…”
Section: M6a‐dependent Regulation Of Rna Functions: Roles Of Specificmentioning
confidence: 97%
“…Recruitment of mRNAs to stress granules is sequestered from translational sites, a process induced by cellular stress (Khong et al . ). This is consistent with the general association of m6A with translational activation.…”
Section: M6a‐dependent Regulation Of Rna Functions: Roles Of Specificmentioning
confidence: 97%
“…It has been a commonly accepted notion that SG formation upon stress induction contributes substantially to the global translational shutdown. However, a recent study using RNA-sequencing and single-molecule fluorescence in situ hybridization (smFISH) showed that only 10–12% of total mRNA molecules are localized to SGs [156], which does not support the notion that SGs are indispensable for global suppression of translation. Indeed, a previous study showed global translational shutdown upon stress induction in cells with G3BP mutations that prohibit SG formation [157].…”
Section: Protein Toxicity In the Stress Granulesmentioning
confidence: 99%
“…The principles and forces governing LLPS are currently extensively studied, not only by in vitro assays using purified BioMC components but also by using in vivo model systems . While many constituent molecules of particular BioMCs have already been identified, and both overexpression as well as genetic deletion approaches of proteins and RNAs are being used to modulate the formation and dynamics of BioMCs, it still remains largely unclear which signals and specific factors trigger the separation of membrane‐less macromolecular assemblies within complex environments. Equally unclear is how cells manage to avoid constant solidification of highly condensed matter in any intracellular compartment and which intracellular changes and molecular activities are required to efficiently maintain a liquid‐like state while dissolving BioMCs when physiologically necessary (i.e., during stress recovery).…”
Section: Dynamic Liquid–liquid Phase Separation Is Key For Proper Celmentioning
confidence: 99%